TMOD-03. SOMATIC MUTATIONS OF CHROMATIN REGULATOR Kmt2d IN CEREBELLAR PRECURSORS INFLUENCES SHH-MEDULLOBLASTOMA TUMORIGENESIS. (11th November 2019) - Sanghrajka, Reeti; Tan, I-li; Wojcinski, Alexandre; Rallapalli, Harikrishna; Turnbull, Daniel; Ge, Kai; Joyner, Alexandra
Abstract: Medulloblastoma (MB), the most common malignant pediatric brain tumor, is a classic example of dysregulation of developmental pathways leading to tumorogenesis. Despite advancements in multi-modal therapies, most patients suffer from long-term neurocognitive and neuroendocrine disabilities. The Sonic Hedgehog subgroup of MB (SHH-MB) accounts for ~30% of all cases and originates from ATOH1+ cerebellar granule cell precursors (GCPs). Experimental data in mice has shown that activating mutations in the SHH pathway induce tumors only in rare GCPs, suggesting that additional mutations and epigenetic changes are required to influence tumor progression. The KMT2D gene, encoding the histone-lysine N-methyltransferase 2D, is amongst the ten most frequently mutated genes in MB, with somatic mutations seen in ~15% of all SHH-MB patients. We developed sporadic mouse models of SHH-MB with a low penetrance to enable studies of secondary mutations (Tan, PNAS, 2018). Immunofluorescence staining for KMT2D on early-stage SHH-MB lesions, mid-stage and late-stage tumors revealed that a subset of lesions/tumors (16/98) do not express KMT2D and are negative for H3K4me3. Interestingly, P53 and KMT2D expression showed a positive correlation in ~94% of tumors/lesions and NeuN and KMT2D showed a positive correlation in ~92% of tumors/lesions. In order to determine the roles for KMT2D in GCP proliferation and differentiation, and uncover whether and how KMT2D promotes SHH-MB tumorigenesis, we are using genetic mouse-models whereby Kmt2d is heterozygously or homozygously deleted alone, or in conjunction with activation of the SHH pathway. Mice with SHH-MB tumors expressing SmoM2 and a loss of Kmt2d develop aggressive tumors at high penetrance, with metastatic leptomeningeal spread in the brain stem and spinal cord. Thus, loss of Kmt2d increases SHH-MB tumor progression and leads to malignancy. Ongoing studies are determining how the chromatin landscape and gene expression are changed when Kmt2d is deleted in GCPs.